Det gyldne øjeblik i parforholdet - Jacobsen, Linda Stub Korsgaard; Steenberger, Signe; Trillingsgaard, Tea (Psyke & Logos, 2016)
A substantial amount of knowledge has recently been generated on the potential of psychological practices such as mindfulness, that cultivates the individual’s capacity to become more consciously aware of the mind’s present experiences. Yet, we know less about the potential of conscious awareness of those present moments when the minds of two people meet, moments that Stern (2004) defines as moments of meeting. This paper presents the ‘The Golden Moment’ intervention; a 15-minute guided couple interaction exercise that brings the couple’s memories from everyday moments of meeting into the “now” of the therapeutic setting. The purpose of this exercise is to emotionally evoke a positive interaction in the couple, increase emotional intimacy and strengthen the shared couple narrative and identity. In this paper we illustrate the potential of ‘The Golden Moment’, both theoretically and practically through a case analysis. We discuss the potential and limitations of the intervention in relation to existing evidence based couples therapies. We conclude that the intervention has potential, primarily as a strength-focused element to be integrated with existing couples therapies, and secondly as an interpersonal alternative to cultivate the individual mind's journey to self-awareness. ‘The Golden Moment’ can be understood as a simple, though not always easy to implement, intervention that can assist the individual to become more aware of the partner's state of mind.